The added value of three-dimensional transthoracic echocardiography in mitral annular disjunction: a case report - Papadopoulos, Konstantinos; Ikonomidis, Ignatios; Vannan, Mani A. (Frontiers in Cardiovascular Medicine, 2024)
Background: Mitral annular disjunction (MAD) refers to the arrhythmic mitral valve prolapse (MVP) syndrome that is associated with ventricular arrhythmias and sudden cardiac death. The pathophysiology of this disease is still under investigation but there have been recognized specific imaging criteria that establish the diagnosis. In this article we demonstrate all most of these criteria with three-dimensional transthoracic echocardiography (3D-TTE) and we provide the added value in the management of MAD syndrome.A 50 yrs old male patient with recent syncope and known mitral regurgitation (MR) and MAD was admitted to our clinic for further investigation.According to our protocol, the patient underwent a complete 3D-TTE, laboratory blood exams and 24h ambulatory electrocardiogram (ECG). Our investigation confirmed the presence of MAD syndrome with bileaflet prolapse, severe MR and non-sustained ventricular tachycardia for which he received an implantable cardioverter defibrillator (ICD) and underwent surgical mitral valve repair. 3D-TTE analysis of mitral valve demonstrated the mitral annular systolic expansion and systolic flattening of the saddle-shaped annulus, quantified the extend of the disjunction arc, and four-dimensional (4D) strain analysis of the left ventricle revealed the presence of fibrosis of the postero-medial papillary muscle and basal inferolateral wall, variables that are required for the diagnosis and therapeutic management of MAD syndrome.3D-TTE and 4D strain can provide all the necessaryimportant information for the diagnosis and management of the patients with MAD syndrome.